Redefining Architecture Through Posthuman Principles: Bridging Cybernetic Concepts and XR Technologies - Karabağlı, Kaan; Kuran, Ipek (İstanbul Teknik Üniversitesi, 2024)
The integration of cybernetic principles into architectural discourse has led to a profound transformation in the conceptualization of architectural entities. Cybernetics redefines architecture as a dynamic and responsive entity, capable of communication, interaction, and adaptation. This paradigm shift is exemplified by the Fun Palace project, which envisioned architecture as a living organism dynamically responding to its environment. Marcos Novak's concept of liquid architecture further elucidates this transformative paradigm, emphasizing architecture's fluid adaptability in digital realms. Realizing these transformative qualities requires architecture's integration into digital space. Extended Reality (XR) technologies serve as a conduit for this integration, enabling architects to transcend traditional limitations and reshape spatial environments. Through a rigorous inquiry into the convergence of cybernetic principles and XR technologies, this research redefines architecture in the digital age. Two workshops serve as case studies, demonstrating the transformative potential of this symbiotic relationship. In conclusion, this research sheds light on the symbiotic relationship between cybernetic principles, XR technologies, and architectural design, offering insights into transformative possibilities. By redefining architecture in the digital age, this study paves the way for a new era of architectural innovation, where creativity transcends boundaries, and the built environment becomes a dynamic expression of human imagination.

Sibernetiğin mekan üretim pratiklerine entegrasyonu, mimarlığın kavramsallaştırılmasında derin bir dönüşüme yol açmıştır. Sibernetik, mimariyi iletişim kurabilen ve adaptasyon becerisi yüksek, dinamik ve etkileşimli bir yapı olarak yeniden tanımlamamızı sağlar. Bu paradigma değişimi, mekanı çevreye dinamik olarak tepki veren canlı bir organizma olarak ele alan Fun Palace projesi ile görünür hale gelir . Marcos Novak'ın akışkan mimari kavramı, mimarinin dijital alanlardaki akışkan uyarlanabilirliğini vurgulayarak bu dönüştürücü paradigmayı güçlendirmektedir. Bu dönüştürücü nitelikleri ortaya koyabilmek, mekanın dijital ortamda varolmasıyla mümkün olabilir. Genişletilmiş Gerçeklik (XR) teknolojileri bu entegrasyon için bir kanal görevi görerek mimarların geleneksel sınırlamaları aşmasına ve mekansal ortamları yeniden şekillendirmesine olanak tanımaktadır. Sibernetik ilkeler ile XR teknolojilerinin yakınsamasına ilişkin olan bu araştırma, dijital çağda mimariyi yeniden tanımlar. İki çalıştay, bu simbiyotik ilişkinin dönüştürücü potansiyelini gösteren örnek olay çalışmaları olarak hizmet ermektedir. Sonuç olarak bu araştırma, sibernetik ilkeler, XR teknolojileri ve mimari tasarım arasındaki simbiyotik ilişkiye ışık tutarak dönüştürücü olasılıklara dair içgörüler sunmaktadır. Bu çalışma, mimariyi dijital çağda yeniden tanımlayarak, yaratıcılığın sınırları aştığı ve yapılı çevrenin insan hayal gücünün dinamik bir ifadesi haline geldiği yeni bir mimarlık tanımı getirmektedir.
Posthuman İlkeleri ile Mimarlığı Yeniden Tanımlamak: Sibernetik ile XR Teknolojilerinin Entegrasyonu
Keywords: Post-human architecture; Cybernetic principles; Extended reality technologies; Architectural ecosystems; Symbiotic harmony; Posthuman Mimari; Sibernetik İlkeler; Genişletilmiş Gerçeklik Teknolojileri; Mimari Ekosistemler; Simbiotik Harmoni